‘Strikingly and stubbornly high’: Investigating the paradox of public confidence in the Irish police - Hamilton, Claire (European journal of criminology, 2023)
While levels of public confidence in the police have declined internationally, the Republic of Ireland appears to have bucked this trend with confidence levels that remain ?strikingly and stubbornly high? ( Mulcahy, 2016: 275). This situation appears all the more puzzling given the wave of scandals to have hit the force in recent decades, ranging from police corruption in Donegal in the late 1990s to a more recent whistleblower scandal that has resulted in the resignation of a slew of Ministers and high-ranking officials. Such developments beg important questions as to the factors sustaining public confidence over this tumultuous period. Drawing on international and domestic data, this article aims to probe this ?paradox? of public confidence in the Irish police. It argues that, although confidence is high, there is more to the dynamics of confidence in the police in Ireland than this initial appraisal suggests. Indeed, it advances the Irish case as an illustration both of the dimensionality of the public confidence concept and the complexity of the pathways to trust in the police.